Pengaruh Komitmen Organisasi dan Budaya Organisasi, terhadap Organizational Citizenship Behavior, baik secara parsial maupun simultan pada PT. Pleno Anugrah Dinamika Jakarta - Hadiwijaya, Dudung (JMB : Jurnal Manajemen dan Bisnis, 2024)
The purpose of this study was to determine the effect of Organizational Commitment and Organizational Culture, on Organizational Citizenship Behavior, either partially or simultaneously at PT. Pleno Anugrah Dinamika Jakarta. This study uses an associative method with a quantitative approach. Sampling was 109 people with techniques are questionnaires. Descriptive data analysis and inferential statistical analysis is for hypothesis testing. Data processing is assisted by Microsoft Excel and SPSS version 25 software. Based on the Organizational Commitment (X1) correlation test, and Organizational Culture  (X2) with Organizational Citizenship Behavior (Y) has a strong relationship. While the contribution of Organizational Commitment (X1) and Organizational Culture (X2) to Organizational Citizenship Behavior (Y) is 31%. Based on multiple regression tests it shows that, the higher the value of Organizational Commitment (X1) and Organizational Culture (X2) simultaneously at a certain value, then it will increase the value of Organizational Citizenship Behavior (Y) at a certain value as well. The simultaneous effect of Organizational Commitment and Organizational Culture on Organizational Citizenship Behavior at PT. Pleno Anugrah Dinamika Jakarta is significant. Partially Organizational Commitment has a positive and significant effect on Organizational Citizenship Behavior, and Organizational Culture has a positive and significant effect on Organizational Citizenship Behavior  at PT. Pleno Anugrah Dinamika Jakarta